(3RHOI GdWH aj GdeYGdLGJs - (3CHh EHQGgje , ESeGYjd Hf GdMSf GdMSjfj GdLQLGfj,J (B531 (3g` s ((3eMeO Hf YeQ Hf eMehO GdMSjfi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg SHMGfg aGYde Cf eHfi GdWH heOGQ CeQg Ydi eYQaI MGdJi HOf GdEfSGf ef GdUMI hGdeQV , hdG jJe eYQaJgG hGdGSJOdGd Ydi cd hGMO efgeG EdG HeYQaI CMhGd GdfHV hGdJfaS s
(3BNQgG (B:s
(3GdMjhGf GdeYQha HONGd GdCPf (B: (3jMOK efg hLY TOjO , jScf HYO SGYI , hQHeG cai ajg ajg GSJYeGd GdedM eY GdNd s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B117 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B952 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B295 s
Keywords: (3GdWHs